The role of mechanical signals in regulating chondrogenesis and osteogenesis of mesenchymal stem cells - KELLY, DANIEL (My University, 2010)
It is becoming increasingly clear that mesenchymal stem cell (MSC) differentiation is regulated by mechanical signals. Mechanical forces generated intrinsically within the cell in response to its extracellular environment, and extrinsic mechanical signals imposed upon the cell by the extracellular environment, play a central role in determining MSC fate. This article reviews chondrogenesis and osteogenesis during skeletogenesis, and then considers the role of mechanics in regulating limb development and regenerative events such as fracture repair. However, observing skeletal changes under altered loading conditions can only partially explain the role of mechanics in controlling MSC differentiation. Increasingly, understanding how epigenetic factors, such as the mechanical environment, regulate stem cell fate is undertaken using tightly controlled in vitro models. Factors such as bioengineered surfaces, substrates, and bioreactor systems are used to control the mechanical forces imposed upon, and generated within, MSCs. From these studies, a clearer picture of how osteogenesis and chondrogenesis of MSCs is regulated by mechanical signals is beginning to emerge. Understanding the response of MSCs to such regulatory factors is a key step towards understanding their role in development, disease and regeneration. Birth Defects Research (Part C) 90:75?85, 2010
PUBLISHED
Keywords: Bioengineering; mesenchymal stem cell; osteogenesis; chondrogenesis; mechanobiology; mechano-transduction; bioreactor; Next Generation Medical Devices